Genetic dissection of down syndrome-associated alterations in APP/amyloid-β biology using mouse models - Tosh, Justin L.; Rhymes, Elena R.; Mumford, Paige; Whittaker, Heather T.; Pulford, Laura J.; Noy, Sue J.; Cleverley, Karen; Walker, Matthew C.; Tybulewicz, Victor L. J.; Wykes, Rob C.; Fisher, Elizabeth M. C.; Wiseman, Frances K. (Scientific reports, 2021)
Individuals who have Down syndrome (caused by trisomy of chromosome 21), have a greatly elevated risk of early-onset Alzheimer’s disease, in which amyloid-β accumulates in the brain. Amyloid-β is a product of the chromosome 21 gene APP (amyloid precursor protein) and the extra copy or ‘dose’ of APP is thought to be the cause of this early-onset Alzheimer’s disease. However, other chromosome 21 genes likely modulate disease when in three-copies in people with Down syndrome. Here we show that an extra copy of chromosome 21 genes, other than APP , influences APP/Aβ biology. We crossed Down syndrome mouse models with partial trisomies, to an APP transgenic model and found that extra copies of subgroups of chromosome 21 gene(s) modulate amyloid-β aggregation and APP transgene-associated mortality, independently of changing amyloid precursor protein abundance. Thus, genes on chromosome 21, other than APP, likely modulate Alzheimer’s disease in people who have Down syndrome.